Evaluation of sn-2 fatty acid composition in commercial infant formulas on the Chinese market: A comparative study based on fat source and stage - Sun, Cong; Wei, Wei; Su, Hang; Zou, Xiaoqiang; Wang, Xingguo (Food chemistry, 2018)
•Sn-2 fatty acid composition of formulas and mature human milk (MHM) were compared.•Fat source and stage had significant effects on most of sn-2 fatty acids in formulas.•Significant differences between formulas and MHM were found.•Formulas with OPO had lower proportions of relative PA at the sn-2 position than MHM. The sn-2 fatty acid composition of 180 commercial infant, follow-on and growing-up formulas with three fat sources (plant oil, cows’ milk and goats’ milk) was investigated and compared with mature human milk (MHM). Sn-2 fatty acids in formulas were mostly dependent on fat source and stage. Compared with MHM, all types of formulas contained lower levels of palmitic acid (PA), saturated fatty acid and long-chain polyunsaturated fatty acids (LC-PUFA), and higher levels of oleic acid (OA), linoleic acid (LA) and α-linolenic acid (LNA) at the sn-2 position. Even some formulas were supplemented with 1,3-dioleoyl-2-palmitoylglycerol, the proportions of relative PA at the sn-2 position in formulas were much lower than that in MHM. Moreover, formulas had higher proportions of relative OA, LA and LNA, and lower LC-PUFAs at the sn-2 position. This study indicated that there were significant differences in the positional distribution of fatty acids between formulas and MHM.